2006
DOI: 10.1002/hlca.200690218
|View full text |Cite
|
Sign up to set email alerts
|

2,5‐Dihydro‐1H‐imidazole‐Based Nitroxides as Prospective Mediators in Living Radical Polymerization

Abstract: Dedicated to the memory of Professor Hanns FischerA number of spectroscopic methods were applied to obtain kinetic parameters of reactions modelling the 2,5-dihydro-1H-imidazole 1-oxide mediated living polymerization of acrylates. The homolysis rate constants of alkoxyamines based on five nitroxides were measured by EPR spectroscopy at different temperatures. The recombination rate constants k c between the corresponding alkyl radicals and the nitroxides were measured by means of laser flash photolysis. The ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…Nitroxides 1 •,30 2 •,30 5 •,31 6 •,32 7 •,20 10 •,33 12 •,19 16 •– 21 •,19, 34, 35 and alkoxyamines20 1a , 2a , 7d , 17e,g , and 18a were prepared as reported. Solvents for synthesis – 1‐bromoethylbenzene, 2‐bromo‐2‐methylpropionic acid methyl and tert ‐butyl ester, methyl and tert ‐butyl, bromo‐2‐methylpropionyl bromide, copper metal, copper bromide, N , N , N ′, N ′, N ″ ‐ pentamethyldiethylenetriamine (PMDETA), benzene, chlorobenzene and tert‐ butylbenzene – were purchased from Aldrich and used as received.…”
Section: Experimental Partmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitroxides 1 •,30 2 •,30 5 •,31 6 •,32 7 •,20 10 •,33 12 •,19 16 •– 21 •,19, 34, 35 and alkoxyamines20 1a , 2a , 7d , 17e,g , and 18a were prepared as reported. Solvents for synthesis – 1‐bromoethylbenzene, 2‐bromo‐2‐methylpropionic acid methyl and tert ‐butyl ester, methyl and tert ‐butyl, bromo‐2‐methylpropionyl bromide, copper metal, copper bromide, N , N , N ′, N ′, N ″ ‐ pentamethyldiethylenetriamine (PMDETA), benzene, chlorobenzene and tert‐ butylbenzene – were purchased from Aldrich and used as received.…”
Section: Experimental Partmentioning
confidence: 99%
“…In recent reports, it was shown that the k c values for the recombination of alkoxycarbonyl‐2‐prop‐2‐yl,19, 20 alkoxycarbonylethyl,19, 20 and 1‐phenylethyl21 radicals – models for the corresponding propagating polymer radicals – with two new families of nitroxides – imidazolidin‐ N‐ oxyl and imidazolin‐ N‐ oxyl radicals (Figure 1) – were in a suitable range ( k c > 10 6 L · mol −1 · s −1 ) for the NMP of the corresponding monomers. Few years ago Aldebbagh et al22, 23 and Chong et al24 showed with some homologues (5‐membered ring nitroxides exhibiting a CO in position 3 of the ring) the possibility of appling alkoxyamines based on such type of nitroxides as initiators/controller for NMP.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, NMP of alkyl methacrylates, in particular methyl methacrylate (MMA), is very demanding, although a number of attempts using different nitroxides or alkoxyamines have been performed 10–19. The main complication for NMP of MMA is the occurrence of side reactions, namely, the intramolecular β‐proton transfer (IPT, Cope‐type elimination20), intermolecular β‐hydrogen atom transfer (IHAT) reactions (reactions (ii) and (iv), respectively, in Scheme ), irreversible decomposition of dormant species (i.e., through NO bond homolysis),21–23 and decomposition of persistent nitroxyl radicals in the course of NMP.…”
Section: Introductionmentioning
confidence: 99%
“…Alkoxyamines were prepared as previously reported for 1a [19], 2a [20], 3a [21]. Deuterated solvents and PhSH were purchased from Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%